Exploring gender's differences on purchase intentions of prototypical and me-too brands - Quintal, Vanessa; Sims, Daniel (School of Marketing, Curtin Business School, 2009)
The current study examines gender's differences on self-confidence, perceived quality, extrinsic attributes, perceived risk and purchase intentions of prototypical and me-too brands from a Generation Y perspective. A pen and paper survey was administered to 348 students at three Australian universities. Males held significantly higher perceived social/physical and financial/performance risks than females for the prototypical brand. Males also demonstrated significantly higher perceived social/physical and time risks than females for the me-too brands. However, males had significantly higher self-confidence in both the prototypical and me-too brands, and also higher purchase intentions for the me-too brands than females. Understanding the factors underlying Generation Y's consumer behavior is important due to their considerable consumption potential and the increasing sophistication of brands in the marketplace.